"Candidatus Liberibacter solanacearum": An Emerging Pathogen Infecting Potato and Tomato - Binoy Babu; Mathews L. Paret; Nicholas Dufault; Carrie L. Harmon (EDIS)
A bacterium called “Candidatus Liberibacter solanacearum” infects potatoes and tomatoes, causing zebra chip in potatoes and psyllid yellows in tomatoes. These diseases are highly destructive and have been known to reduce yields by up to 85%. “Ca. L. solanacearum” has been reported in several states, though it has not been detected in Florida, which is the second largest producer of tomatoes and seventh largest producer of potatoes in the US. This 9-page fact sheet covers the biology, distribution, symptoms, transmission, diagnosis, and management of the pathogen and its associated diseases. Written by Binoy Babu, Mathews L. Paret, Nicholas Dufault, and Carrie L. Harmon, and published by the UF Department of Plant Pathology, August 2015.